Personal issues: Tolerant people (Journal of Parents and Teachers, 1995)
Tolerance is learned in the family and is fostered through an environment of respect and freedom of expression. Intolerance arises from superiority, fear of losing power and lack of openness to new ideas. Coexistence improves when we avoid speaking ill of others and promote constructive solutions.
Keywords: tolerance; intolerance; coexistence; respect